Zinc Oxide Therapy Increases Prevalence and Persistence of Methicillin‐Resistant Staphylococcus aureus in Pigs: A Randomized Controlled Trial. (11th September 2014) - Slifierz, M. J.; Friendship, R.; Weese, J. S.
Summary There is concern that therapeutic use of zinc oxide (ZnO) in swine production may select for methicillin‐resistant Staphylococcus aureus (MRSA) due to co‐location of the zinc resistance gene (czrC) and methicillin resistance gene (mecA) within the staphylococcal cassette chromosome mec (SCCmec). The objective of this investigation was to determine whether MRSA carriage in pigs is influenced by exposure to therapeutic doses of in‐feed ZnO (3000 mg/kg) when compared to the recommended dietary levels (100 mg/kg). A randomized controlled trial was completed using 110 pigs that were naturally colonized with czrC‐positive MRSA. The pigs were followed from birth to weaning (21 d), at which point they were randomized into 8 pens and exposed to either a control feed (100 mg ZnO/kg feed; n = 49 pigs) or a treatment feed (3000 mg ZnO/kg feed; n = 50 pigs); neither feed contained additional antimicrobials. MRSA carriage was monitored weekly in each group for 4 weeks post‐weaning. The prevalence of MRSA was significantly higher in the treatment group at 1‐week (OR = 18.1; P < 0.01) and 2 weeks (OR = 3.01; P = 0.01) post‐weaning when compared to the control group, but there was no difference later in the nursery phase. Persistent MRSA carriage (testing positive ≥2 times post‐weaning) was observed in 2% (1/49) of control pigs and 22% (11/50) of treated pigs (P < 0.01). All MRSA isolates (spa types t034 and t3075) carried czrC and showed uniform resistance to zinc. These findings demonstrate that the prevalence and persistence of MRSA in nursery pigs can be affected by high levels of in‐feed ZnO in the absence of antibiotics.